Exploring the needs and experiences of the social worker as an intermediary - Jarman, Renette (Rhodes University, Faculty of Humanities, Department of Social Work, 2000)
During this research an attempt was made to gain an understanding of the experiences and needs of the social workers acting as intermediaries for the sexually abused children in the criminal court during the trials of perpetrators. To achieve this, ten social workers that have performed the role of intermediary were interviewed. Research as well as literature on this topic is limited and it is believed that this study will present a valuable basis to pursue in further research as well as assist social workers already rendering intermediary services. Literature that was available was found to be critical of the adversarial system and the negative elements associated with the system, especially for the child witness. The study found that there are many problems associated with the intermediary system. The most important issue is the delay between the decision to prosecute and the trial as this impacts negatively on the child witness. In addition social workers acting as intermediaries are inadequately trained and are not supervised in this role. As a result very few are willing to continue with the procedure. Nevertheless the intermediary system is adjudged better than the adversarial system, especially as the child witness no longer has to face the alleged perpetrator in an open court. The thesis ends with recommendations for addressing the concerns of intermediaries in order to strengthen the system.
Keywords: Social workers; Mediation